2012
DOI: 10.1111/twec.12020
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Imports in Enhancing Manufacturing Exports

Abstract: Making use of a large panel data set on Italian manufacturing firms, we provide evidence on the effect of imports on the firm's export performance. We distinguish imports of intermediates according to their origin, and we find that inputs sourced from low labour cost countries promote the firm's export activity. Imports from high‐income countries do not significantly contribute to the export orientation of firms, especially when both persistence in export and the possible endogeneity of the import measures are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 54 publications
2
29
1
1
Order By: Relevance
“…Studies for Argentina's manufacturing sector (Bas, ) and France's agrifood sector (Chevassus‐Lozza, Gaigne, & Mener, ) focusing on input tariff liberalisations as well as for Italy's manufacturing sector (Lo Turco & Maggioni, ) focusing on the actual use of imported intermediate inputs show that those increase firms’ propensity to export and firms’ total exports . More recent studies for the manufacturing sectors in France (Bas & Strauss‐Kahn, ) and China (Bas & Strauss‐Kahn, ; Feng, Li, & Swenson, ) show that the use of imported intermediate inputs leads firms to increase their likelihood of exporting, their export scope or their export quality.…”
Section: Introductionmentioning
confidence: 99%
“…Studies for Argentina's manufacturing sector (Bas, ) and France's agrifood sector (Chevassus‐Lozza, Gaigne, & Mener, ) focusing on input tariff liberalisations as well as for Italy's manufacturing sector (Lo Turco & Maggioni, ) focusing on the actual use of imported intermediate inputs show that those increase firms’ propensity to export and firms’ total exports . More recent studies for the manufacturing sectors in France (Bas & Strauss‐Kahn, ) and China (Bas & Strauss‐Kahn, ; Feng, Li, & Swenson, ) show that the use of imported intermediate inputs leads firms to increase their likelihood of exporting, their export scope or their export quality.…”
Section: Introductionmentioning
confidence: 99%
“…The latter choice allows to account for the actual importance of importing within the overall firm activity. Secondly, from the recent evidence on the strict linkage between importing and exporting (Muûls and Pisu 2009;Kasahara and Lapham 2008;Aristei et al 2011;Lo Turco and Maggioni 2012b) and on learning-by-exporting, throughout our work we dissect the role of importing once accounted for the role of exporting too. Finally, our focus on the Italian case can be considered of particular interest.…”
Section: Introduction and Relevant Literaturementioning
confidence: 85%
“…As a matter of fact, established literature suggests that exporting may importantly shape the firm efficiency (Van Biesebroeck 2005;De Loecker 2007;Maggioni 2012) and the existence of such learning effects stemming from the firm penetration of foreign markets has been detected for Italy (Serti and Tomasi 2008a). Resting on the latter finding together with the evidence of a strict linkage existing between the purchasing of foreign inputs and the export activity (Castellani et al 2010;Lo Turco and Maggioni 2012b), it emerges the need to control for the impact of exports on firm efficiency. Its omission might erroneously deliver a significant effect of imports on productivity even when there is a simple spurious correlation.…”
Section: Introduction and Relevant Literaturementioning
confidence: 99%
“…This is studied by Aristei et al (2013) who used firm-level survey data from 27 countries and found that a firm's importing increases its exports while a firm's exporting does not have any effect on its imports. Turco and Maggioni (2013) did a similar analysis for Italian firms and found that importers are more likely to start exporting. Muûls and Pisu (2009) found that export status is positively correlated with both previous export and import experience and vice versa, confirming that there are substantial sunk costs of entry.…”
Section: Introductionmentioning
confidence: 89%